(3GdeTcdGJ hGdSjGSGJ GdebJQMI eY ETGQI Edi GdHdOGf GdYQHjIs - (3YHO GdhgGH(B, (3GdCejfs ((3LOI(B:s (3OGQ MGaX(B,s, 2000)
(3eaghe GdJfejI hGdCgOGa hGdSjGSGJ GdGfeGFjI GdeWdhHI(B-(3NUGFU GdHdOGf GdfGejI(B-(3fXQjGJ GdJfejI GdGbJUGOjI(B-(3Gdfeh GdGbJUGOj,GdabQ,hJhRjY GdONd Gdbhej(B-(3feh GdScGf hGdJfejI GdGbJUGOjI(B-(3GdJYdje hGdJfejI(B-(3OhQ GdRQGYI aj GdJfejI GdGbJUGOjI(B-(3GdJLGQI GdOhdjI hGdJfejI GdGbJUGOjI(B-(3eTcdI GdeOjhfjI GdNGQLjI ddHdOGf GdfGejI(B-(3GdJNWjW GdGfeGFj(B-(3GdGUdGMGJ GdGbJUGOjI(B-(3GdHjFI hGdJfejI GdeSJOGeI(B-(3GdGfaGb GdYScQj hGdJfejI GdGbJUGOjI(B-(3Mbhb GdGfSGf hGdJfejI GdeSJOGeI (B-(3GdHdOGf GdfGejI hGdfXGe GdGbJUGOj GdYGdej GdLOjOs
Keywords: (3GdGbJUGOs; (3GdJfejI GdGbJUGOjIs; (3GdScGfs